Controlling for Landform Age When Determining the Settlement History of the Kuril Islands. Issue 3 (28th March 2014) - MacInnes, Breanyn; Fitzhugh, Ben; Holman, Darryl; Buvit, Ian; Carson, Mike T.
<x xml:space="preserve">Abstract</x> Archaeological investigations of settlement patterns in dynamic landscapes can be strongly biased by the evolution of the Earth's surface. The Kuril Island volcanic arc exemplifies such a dynamic landscape, where landscape‐modifying geological forces were active during settlement, including sea‐level changes, tectonic emergence, volcanic eruptive processes, coastal aggradation, and dune formation. With all these ongoing processes, in this paper we seek to understand how new landscape formation in the Holocene might bias archaeological interpretations of human settlement in the Kurils. Resolving this issue is fundamental to any interpretation of human settlement history derived from the distribution and age of archaeological sites from the region. On the basis of a comparison of landform ages and earliest archaeological occupation ages on those landforms, we conclude that landform creation did not significantly bias our aggregate archaeological evidence for earliest settlement. Some sections of the archipelago have larger proportions of landform creation dates closer to archaeological evidence of settlement and undoubtedly some archaeological sites have been lost to geomorphic processes. However, comparisons between regions reveal comparable archaeological establishment patterns irrespective of geomorphic antiquity.